EFFORTS TO INCREASE COLORING CREATIVITY THROUGH IMAGE MEDIA - Widya Masitah; Widdia Sista Ariani (Proceeding International Seminar of Islamic Studies, 2022)
Kindergarten (TK) education is a bridge between the family environment and the wider community, namely elementary schools and other environments. Realizing the importance of this, providing early education services is necessary. Coloring learning for early childhood is one way to stimulate children's motor development. By learning to color, one of the advantages is that it will be able to increase children's creativity. This creativity can actually be developed in various ways and can be done anywhere either in the family environment or also in the environment where children interact (Lubis et al., 2016). This research was conducted to see the development of coloring creativity in One Roof Kindergarten children at SDN 2 Rimo, Lae Butar village, Gunung Meriah sub-district, Aceh Singkil district, totaling 20 students in class B. The activities carried out in this study were coloring through pictorial media. The data collection tool obtained from this study is the work of children.